1997
DOI: 10.1152/jappl.1997.83.6.1814
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of mucosal folding in normal and asthmatic airways

Abstract: Previous studies have demonstrated that the airway wall in asthma and chronic obstructive pulmonary disease is markedly thickened. It has also been observed that when the smooth muscle constricts the mucosa buckles, forming folds that penetrate into the airway lumen. This folding pattern may influence the amount of luminal obstruction associated with smooth muscle activation. A finite-element analysis of a two-layer composite model for an airway is used to investigate the factors that determine the mucosal fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
259
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(273 citation statements)
references
References 20 publications
13
259
1
Order By: Relevance
“…These regions would be directly exposed to without the influence of the surface film. Additionally, airway walls are not smooth and have ridges and folds; the ratio of the height of the ridges to the diameter will be amplified during constriction (35). The in a nonsmooth walled tube are amplified, depending on the ratio of the height of the ridge and the airway diameter (12).…”
Section: Shear Stress Amplification In Heterogenous Constrictionmentioning
confidence: 99%
“…These regions would be directly exposed to without the influence of the surface film. Additionally, airway walls are not smooth and have ridges and folds; the ratio of the height of the ridges to the diameter will be amplified during constriction (35). The in a nonsmooth walled tube are amplified, depending on the ratio of the height of the ridge and the airway diameter (12).…”
Section: Shear Stress Amplification In Heterogenous Constrictionmentioning
confidence: 99%
“…In the work reported here, we use a unique coculture system of mechanically stressed human bronchial epithelial cells (HBECs) and unstressed human lung fibroblasts (HLFs) to investigate whether the two cell types communicate with each other in response to the mechanical stress in a way that is relevant to matrix remodeling. The mechanical stress was applied in the form of a hydrostatic pressure difference across the epithelial cell layer to mimic the normal stresses that develop in the folds of a buckled airway (12). Cocultured fibroblasts were not exposed to a mechanical stimulus but were in contact with the epithelial layer via soluble mediators.…”
mentioning
confidence: 99%
“…To ponder the physiological relevance of the strain we applied to our in vitro models, we first considered that the strain magnitude within any bronchoconstricted airway wall is highly nonuniform; SMCs on the outer perimeter shorten to cause compression of the airway wall (25), but since the internal perimeter remains constant (maintained by the basement membrane), the epithelium buckles into the lumen (34,40,58,74). Furthermore, strain varies radially from the epithelium to the subepithelium due to geometry, buckling, and different mechanical properties of epithelial vs. subepithelial regions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, strain varies radially from the epithelium to the subepithelium due to geometry, buckling, and different mechanical properties of epithelial vs. subepithelial regions. Finally, strain profiles are different in bronchoconstricted airways of normal vs. asthmatic patients, because of the mechanics and increased thickness of the remodeled airway wall (35,53,54,74) as well as increased contractile forces of asthmatic SMCs (8,25,57). A number of studies (29,30,32,34,47,58) have shown that in models of induced (e.g., by methacholine or histamine) bronchoconstriction, the maximum level of SMC shortening (i.e., that which causes complete closure of the lumen) is 30 -40%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation